Does the effect of revealed private information on initial public offering (IPO) first trading day return differ by IPO market heat?. (14th March 2013) - O'Connor Keefe, Michael; Gallagher, David
Abstract By IPO market regime, I decompose the effect of revealed private information on the initial return of IPOs (initial public offerings) into adjusted and unadjusted private information and find (i) investment banks partially adjust the offer price in return for revealed private information in all but the non‐hot IPO market; (ii) the economic importance of private information associated with IPOs (and hence agency costs) is procyclical; and (iii) industry information spillovers between IPOs occur only in the hot and very‐hot IPO markets.